2021
DOI: 10.3390/v13040548
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Sargassum fusiforme and Its Components on Replication of Respiratory Syncytial Virus In Vitro and In Vivo

Abstract: Sargassum fusiforme, a plant used as a medicine and food, is regarded as a marine vegetable and health supplement to improve life expectancy. Here, we demonstrate that S. fusiforme extract (SFE) has antiviral effects against respiratory syncytial virus (RSV) in vitro and in vivo mouse model. Treatment of HEp2 cells with a non-cytotoxic concentration of SFE significantly reduced RSV replication, RSV-induced cell death, RSV gene transcription, RSV protein synthesis, and syncytium formation. Moreover, oral inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Plain-NE was also examined, showing IC 50 values of 45.24 μg/mL against HAV and 42.11 μg/mL against HSV-1. Several constituents in the chemical composition of both EOs were reported to have antiviral activity, such as linalool [ 41 ], nerolidol [ 42 ], and straight chain hydrocarbon compounds (acyclic alkanes) e.g., tetracosane [ 43 ], and nonacosane [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Plain-NE was also examined, showing IC 50 values of 45.24 μg/mL against HAV and 42.11 μg/mL against HSV-1. Several constituents in the chemical composition of both EOs were reported to have antiviral activity, such as linalool [ 41 ], nerolidol [ 42 ], and straight chain hydrocarbon compounds (acyclic alkanes) e.g., tetracosane [ 43 ], and nonacosane [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has also exhibited antiviral activity (Sun et al, 2021). A previous study demonstrated that treatment of HEp2 cells with S. fusiforme extracts in non-cytotoxic concentrations could led to an obvious decrease of respiratory syncytial virus (RSV) replication, RSV gene transcription, RSV protein synthesis, RSV-induced cell death, and syncytium formation (Chathuranga et al, 2021). Sun et al also reported that, upon treatment with S. fusiforme extracts, the gene and protein expressions of the avian leukosis virus subgroup J (ALV-J) were clearly reduced (Sun et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In some research studies, chemical components in S. fusiforme also showed antiviral and antibacterial effects. ,, Ahmed et al obtained crude extracts of different solvents ( n -hexane, ethyl acetate, and ethanol) from S. fusiforme , and extracted flavonoids and alkaloids. They used a well diffusion assay to detect the effects of the obtained substances on bacterial pathogens inflicting gross lesions in corals (such as Vibrio owensii , Emperobacter brevis , Provincia vermica , and Brevibacterium linens ) .…”
Section: Bioactivities Of S Fusiformementioning
confidence: 99%